Smaller infarct size with ticagrelor vs. clopidogrel in STEMI patients: Insights from cardiac magnetic resonance - Francisco A Fonseca; Adriano Caixeta; Gilberto Szarf; Ibraim Pinto; Antonio M Figueiredo Neto; Carolina N França; Henrique T Bianco; Henrique A Fonseca; Amanda S Bacchin; Michelle Birtche; Igor R M Batista; Maria C Izar (PLoS ONE, 2025)
Background Ticagrelor has many protective cardiovascular properties beyond potent antiplatelet action. This study aimed to compare the effects of ticagrelor versus clopidogrel on infarcted mass, quantified by cardiac magnetic resonance (CMR), in patients with ST-segment elevation acute myocardial infarction (STEMI). Methods Adult patients of both sexes with STEMI under a pharmaco-invasive strategy were included (n = 225). Patients were treated by thrombolysis within six hours of symptom onset and underwent angiography with percutaneous coronary interventions, when needed, within the first 24 hours. Prior to the invasive procedures, patients were randomly assigned to receive either ticagrelor or clopidogrel using a centralized computerized system. Patients were followed on a weekly basis to optimize their medical therapy. Results After 30 days, CMR was performed and a smaller percentage of left ventricular infarcted mass was found with ticagrelor (p = 0.012), despite similar angiographic findings at baseline (Syntax score, Gensini score, culprit artery, TIMI flow, and myocardial blush). At 30 days, left ventricular ejection fraction (LVEF) was comparable between groups. Still, the K-means algorithm displayed more homogeneous responses for smaller infarcted mass and better LVEF among those patients treated with ticagrelor. Standard lipid panel and most inflammatory parameters were similar at baseline and after 30 days. However, lower high-sensitivity troponin T and high-sensitivity C-reactive protein levels were found in samples collected from patients treated with ticagrelor on the first day of STEMI. Conclusion In patients with STEMI under a pharmaco-invasive strategy, therapy with ticagrelor was associated with a smaller infarct size than clopidogrel. Trial registration Clinicaltrials.gov ( NCT02428374 ).